Blade Shape Analysis on The Performance of The Pelton Turbine Prototype - Yani, Ahmad; Irianto, Irianto; Triyatno, Joko; Fitria, Fitria; Sobah, Saripah (Politeknik Negeri Ujung Pandang, 2020)
Water turbine is one of the driving machines where the working fluid is water that is used directly to spin the turbine runner. This research was conducted using a pelton type water turbine installastion with variations In the shape of the turbine blade. The research method used is an experimental method with a laboratory scale experimental design as well as the results of the design of this water turbine used as a practical tool for students majoring in mechanical engineering. The results showed the influence of turbine blade shape on the performance of the pelton water turbine prototype, so it can be concluded that the maximum tangential velocity is 12.141 rad/s, the hydraulic power value is 2.64 Watts, the kinetic power value is 3.886 Watts, maximum turbine power 99.141 Watts, maximum electric generator power 99.141 Watts, maximum turbine efficiency 25.512 %, and maximum electric generator efficiency 0.661 %.